Role of stilbens in mechanisms hepatoprotective properties of polyphenols Maackia amurensis - V. S. Chuchalin; A. V. Ratkin; Ye. V. Ratkin; V. N. Frolov; V. V. Ivanov; S. A. Fedoreyev; V. P. Bulgakov; S. S. Zorcaltsev (Бюллетень сибирской медицины, 2010)
For finding-out of a role monomer and dimer srilbens in realization hepatoprotective properties of polyphenols maakia amurensis activity of polyphenolic complexes from wood (Maksar), an extract of cellular culture maakia amurensis, and also monomer and dimer srilbens, allocated of a substance Maksar was investigated.Therapeutic efficiency of researched objects was estimated on their influence on survival rate of animals, morphological and biochemical parameters of a liver and wheys of blood of rats with an experimental СCl4-hepatites. It was established, that hepatoprotective influence of Maksar and an extract of cellular culture maakia amurensis is caused by presence of the sums isoflavonoids in their structure. Monomer and dimer srilbens do not show therapeutic activity at an experimental toxic hepatites.